2017
DOI: 10.1557/mrs.2017.142
|View full text |Cite
|
Sign up to set email alerts
|

Electron-emission materials: Advances, applications, and models

Abstract: Electron emission represents the key mechanism enabling the development of devices that have revolutionized modern science and technology. Today, science still relies on advanced electron-emission devices for imaging, electronics, sensing, and high-energy physics. New generations of emission devices are continuously being improved based on innovative materials and the introduction of novel physical concepts. Recent advances are highlighted by emerging low-work-function and low-dimensional materials with unusua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…At a fundamental level, the number of emitted electrons is related to the electrode–vacuum interface barrier height and is important to understand how electrons cross the barrier to reach vacuum level from electrode surface. Multiple stimuli are used to achieve the electron emission, such as thermal‐energy (thermionic emission), photon (photoemission), ion‐electron bombardment (secondary emission), and electric field (field emission) . Diverse theories and formulae have been defined to calculate the electron emission under different conditions and a wide range of material are available in this domain.…”
Section: Generation and Transport Of Electrons (Theory)mentioning
confidence: 99%
“…At a fundamental level, the number of emitted electrons is related to the electrode–vacuum interface barrier height and is important to understand how electrons cross the barrier to reach vacuum level from electrode surface. Multiple stimuli are used to achieve the electron emission, such as thermal‐energy (thermionic emission), photon (photoemission), ion‐electron bombardment (secondary emission), and electric field (field emission) . Diverse theories and formulae have been defined to calculate the electron emission under different conditions and a wide range of material are available in this domain.…”
Section: Generation and Transport Of Electrons (Theory)mentioning
confidence: 99%
“…Various electron sources can be used to emit electrons. In the literature, we can find electron emission sources based on thermal energy [18], field emission (FE) [19], Schottky emission [20], photoemission, and secondary emission [21]. Murphy and Good [19] identified that either one of the primary conditions (temperature or electric field strength) governs electron emission or that an intermediate region exists, where the temperature and electric field both contribute to the electron emission.…”
Section: Basics Of the Fe Cathodesmentioning
confidence: 99%
“…In the last years, following the increasing interest on electron‐emission‐based devices, 1 a hybrid thermionic‐photovoltaic (TIPV) converter was proposed and developed in the frame of European H2020 project AMADEUS for the conversion of stored thermal energy 2 . A TIPV device is constituted of a hot thermionic cathode, able to emit electrons and photons at an operating temperature in the range of 1700–2000 K, and a cooled thermionic anode coupled with a thermo‐photovoltaic (TPV) cell.…”
Section: Introductionmentioning
confidence: 99%